Faktor Yang Memengaruhi Pertumbuhan Laba pada Sektor Industri Subsektor Food and Beverage di Indonesia - Pristha, Anggita Aryunia; Indrati, Menik (Universitas Batanghari, 2024)
This study aims to analyze the impact of liquidity, profitability, solvency, and company size on profit growth. In this research, the independent variable liquidity is measured by CR, profitability is measured by NPM, solvency is measured by DER, and company size is measured by the logarithm of total assets. The dependent variable is profit growth. The objects of this research are food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling, with a total of 9 companies sampled over the period from 2020 to 2023. This study employs multiple linear regression analysis using the Statistical Program for Social Science (SPSS). The results indicate that the liquidity and company size variables negatively affect profit growth, while the profitability variable positively affects profit growth. However, the solvency variable does not impact profit growth. This research can provide insights for companies in formulating policies to enhance their performance by managing assets, debts, and receivables effectively and efficiently to boost profit growth.